'End of life': a concept analysis. (2nd July 2022) - Schüttengruber, Gerhilde; Halfens, Ruud J.; Lohrmann, Christa
Abstract : Background: The concept of end of life (EOL), as in the term end-of-life care, is used synonymously in both palliative and terminal care. Practitioners and researchers both require a clearer specification of the end-of-life concept to be able to provide appropriate care in this phase of life and to conduct robust research on a well-described theoretical basis. Aims: The aim of this study was to critically analyse the end-of-life concept and its associated terminology. Method: A concept analysis was performed by applying Rodgers' evolutionary concept analysis method. Findings: Time remaining, clinical status/physical symptoms, psychosocial symptoms and dignity were identified as the main attributes of the concept. Transition into the end-of-life phase and its recognition were identified as antecedents. This study demonstrates that end-of-life care emerged following the application of the 'end-of-life concept' to clinical practice. Conclusion: The early recognition of the end-of-life phase seems to be crucial to ensuring an individual has well-managed symptoms and a dignified death.